Dork diaries: Sister showdown! - Russell, Rachel Renee; Russell, Nikki & Russell, Erin (Great Britain Simon & Schuster, 2024)
She's back! Nikki Maxwell returns for her 16th Dork Diaries adventure and has to deal with . . . a bratty younger sister. Join the jokes, the drama and the aDORKable BFFs in this mega-selling series with over 50 million copies in print worldwide!
Keywords: Children Fiction